A Query Language With the Star Operator - Lindqvist, Johan; Lundkvist, Torbjörn; Porres, Ivan (Electronic Communications of the EASST, 2007)
Model pattern matching is an important operation in model transformation and therefore in model-driven development tools. In this paper we present a pattern based approach that includes a star operator that can be used to represent recursive or hierarchical structures in models. We also present a matching algorithm, motivating examples and we discuss its implementation in a modeling tool.